Oil Sands Geologists in an Industry-School Partnership: A Resource and Teaching Opportunity - Dudley, Jon; Doram, Ted (Geoscience Canada, 1999)
Summary In some Canadian schools earth science is offered only within general science courses. As a result, science majors may encounter little or no earth science in school. Industry-school partnerships can, however, present an excellent opportunity to overcome this shortcoming. In Alberta, such a partnership developed a credit course within the province's Career and Technology Studies Program on the earth science of oil sands for senior high school science major students. This course, through activity-based workplace site visits, resource material, and teamwork, helps students understand the relevance of their basic sciences as applied in earth science. We hope that this program and its development will be an inspiration and guide for others to initiate similar projects elsewhere in the country.